ENHANCING MOTIVATION TO WORK IN UNEMPLOYED PERSONS: LITHUANIA IN THE CONTEXT OF EU - Gataulinas, Arturas; Zabarauskaitė, Rasa (European Scientific Journal, ESJ, 2014)
This article provides an overview of the research in the area of motivation and activation of the unemployed and analyses work incentives for the unemployed applied in individual OECD and EU countries. In addition, the article provides the analysis of macro-level financial aspects of motivation to work in Lithuania and micro-level findings of a survey of persons registered with the Lithuanian Labour Exchange. It was found out that, in relative terms, employees should be interested in taking up low-paid jobs, but the low wage level does not ensure a decent living in reality. As a result, a relatively high portion of employees prefer undeclared work and social benefits to official employment. Findings of the survey of persons registered with the Lithuanian Labour Exchange have showed that satisfactory pay level is the strongest factor motivating persons to enter the labour market.